Wacław Gdesz, a war “tourist” in the towns of the USSR, Middle East and Europe - Złotkowski, Dariusz (City and War, 2021)
Wacław G desz, a State Police senior l eader in V ilnius. A n internee in Lithuania in1939. He stayed the longest in Palanga. In the summer of 1940, he was taken over by the Russiansand taken to a work camp in the Kola Peninsula. Evacuated with Anders Army to Iran in1942. The trawl of his war “tourism” covered the following places: Iran, Iraq, Palestine, Egypt,Italy and Great Britain. After the liquidation of the Polish armed forces in the West, in Decemberof 1947 he came back to the country. During the whole period of the war he wrote a sortof diary. He put down his everyday impressions and observations. They constitute the basis ofthis article.